Impacts of hydroxyphenylpyruvate dioxygenase (HPPD) inhibitor (mesotrione) on photosynthetic processes in Chlamydomonas reinhardtii. (January 2019) - Xu, Kui; Racine, Francis; He, Zhili; Juneau, Philippe
Abstract: Mesotrione, an herbicide increasingly found in aquatic systems due to its increased application frequency in corn fields, is an inhibitor of the p-hydroxyphenylpyruvate dioxygenase (HPPD), a key enzyme for plastoquinone-9, α-tocopherol and indirectly for carotenoid biosynthesis. The direct effect of mesotrione on plastoquinone-9 and α-tocopherol synthesis and their degradation rates are well documented, but few information exists on its action on photosynthetic processes under various light intensities. We therefore investigated the photosynthetic activity, energy dissipation processes, pigment composition and α-tocopherol content when Chlamydomonas reinhardtii were exposed to mesotrione for 24 h under low light condition and then the impacts of HL treatment (75 min) were also investigated. Under low light growth conditions, mesotrione did not induce PSII photoinhihition, while substantially decreased Car:Chl- a ratio, maximal energy-dependant quenching and state 1 to state 2 transition. Under high light conditions (HL), PSII activity was highly decreased in presence of mesotrione, and the non-photochemical energy dissipation processes were drastically affected in these conditions compared to the HL treatment alone. Mesotrinone also prevent the complete recovery of PSII damage caused by HL. Light condition seems therefore to be a non-negligible factor modulating mesotrione toxicity, and this has an obvious importance in agricultural waterbodies where phytoplankton is subjected to fluctuating light intensities. Graphical abstract: Image 1 Highlights: Mesotrione impacts on Chlamydomonas reinhardtii under two light intensities were studied. Mesotrione affects indirectly carotenoid biosynthesis and chlorophyll content. High light amplifies the effects of mesotrione on energy dissipation and photosynthesis. Mesotrione prevents the complete recovery of PSII photoinhibition. These results have implications for algae living in fluctuating light environments. Abstract : Mesotrione has synergistic effects with high light on pigment content and PSII activity and prevents complete recovery of photoinhibited algae.